Assessment of Respiratory Morbidities among Shopkeepers and Vendors in a Semi-Urban Area - Keny, J. Greeshma; Pandey, Aastha Narayan (Journal of Ecophysiology and Occupational Health, 2023)
Context: Rapid urbanization has increased risk factors for respiratory morbidities, leaving the general population vulnerable. Potentially damaging agents are numerous, which result in damage to defence mechanisms, in turn causing respiratory morbidities. Shopkeepers and vendors in the semi-urban area, who mostly work outdoors at ground level, are continuously exposed to unhealthy environments and practices, and the majority are unaware of the situation. Aim: Our study will help identify the prevalence of respiratory morbidities and their association with risk factors. Thus, appropriate measures could be taken to impede respiratory morbidities. Settings and Design: Cross-sectional study in a semi-urban area. Methods: done among 260 subjects working for more than a year, while ones already on medication for respiratory illnesses were excluded. Statistical Analysis Used: Excel was used for data tabulation and Chi-square tests for significance, with the level of significance at α = 0.05. Results: A high prevalence of respiratory morbidities, with 64.62% of the study population showing one or more respiratory morbidities, was noted. Cough (23.85%), followed by breathlessness (22.31%), and were highly prevalent. The study revealed significant relationships between Peak Expiratory Flow Rate (PEFR) and age, BMI, Total Exposure Period (TEP), respiratory morbidities, and addictions. However, no significant relation was found between PEFR and the type of shop, whereas prevalence was high on the roadside as compared to closed shops. Conclusions: The prevalence was high in subjects with shops situated on the roadside as compared to the closed ones. This was due to the high TEP, as the shopkeepers worked for longer durations owing to their socioeconomic demands. Therefore, the Total Exposure Period (TEP) plays a greater role than the type of shop.